2020
DOI: 10.1186/s12888-020-2456-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain diagnoses and opioid dispensings among insured individuals with serious mental illness

Abstract: Background: Individuals with major depressive disorder (MDD) and bipolar disorder (BD) have particularly high rates of chronic non-cancer pain (CNCP) and are also more likely to receive prescription opioids for their pain. However, there have been no known studies published to date that have examined opioid treatment patterns among individuals with schizophrenia. Methods: Using electronic medical record data across 13 Mental Health Research Network sites, individuals with diagnoses of MDD (N = 65,750), BD (N =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 71 publications
4
22
0
Order By: Relevance
“…Depressive disorder was included as prior work in these health systems and others indicated that it is commonly applied by non-psychiatrists to capture MDD. We adopted this definition for consistency with numerous prior publications 8,3941 applying electronic health records to the study of major depressive episodes. Among those patients, 467 (MGB: 242, VUMC: 225) had at least one procedural code for ECT.…”
Section: Resultsmentioning
confidence: 99%
“…Depressive disorder was included as prior work in these health systems and others indicated that it is commonly applied by non-psychiatrists to capture MDD. We adopted this definition for consistency with numerous prior publications 8,3941 applying electronic health records to the study of major depressive episodes. Among those patients, 467 (MGB: 242, VUMC: 225) had at least one procedural code for ECT.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings align with previous cross-sectional studies indicating an association between opioid misuse and psychiatric disorders. 18 , 19 Several mechanisms might explain this association. For example, the emotional distress associated with psychiatric disorders might predispose to chronic pain and subsequently prolonged opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contrast with previous research showing decreased pain sensitivity in people with a psychotic disorder. 22 , 23 Furthermore, Owen et al 19 found that people with psychotic disorders are less often diagnosed with chronic pain conditions and less often receive opioids than the general population. A potential explanation for the discrepancies between the results of Owen et al and our data is a difference in study design.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is an increasing recognition that chronic pain and mental illness tends to co-occur, with approximately 33% of patients with SMI (Stubbs et al, 2014) experiencing chronic pain. High rates of chronic pain have also been reported by patients with major depressive disorders and bipolar disorders (Owen- Smith et al, 2020;Stubbs et al, 2015aStubbs et al, , 2015bStubbs et al, , 2015c. However, chronic pain has received little attention in people with SMI, despite reduced pain sensitivity (Stubbs et al, 2015a(Stubbs et al, , 2015b(Stubbs et al, , 2015c) and higher severity of pain (Strassnig, Brar, & Ganguli, 2003) reported by people with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%